Laboratory parameters of COVID-19 patients in Khulna, Bangladesh - Chowdhury, Sabikun Nahar; Islam, Md Nazrul; Roshed, Md Mahabubur; Hossain, Md Mokter; Salahuddin, Gazi (Bangladesh Medical Journal Khulna, 2021)
Background: Recent studies have demonstrated the role of several laboratory tests in addition to RT-PCR in the diagnosis of COVID 19. Some of these, laboratory tests are indicators of the current state of the disease, while others have proved to be useful prognostic markers. Objective: The objective of our study was to evaluate the hematological, biochemical and radiological changes in COVID-19 patients. Methods: It was an observational and analytical study done retrospectively. The whole number of patients were included on the basis of inclusion and exclusion creteria. All were confirmed cases of COVID-19 patients either admitted in different hospitals or were in home isolation. Results: Total study cases was 112. Complete blood count revealed, leukocytosis was present in 9 (8.0%) cases and leucopenia in 8 (7.14%) cases. Neutrophilia was present in 27 (24.1%) cases; neutropenia in 9(8.0%) cases, lymphocylosis in 17 (15.2%) cases; lymphopenia in 28 (25%) cases. Neutrophil Lymphocyte ratio (NLR) revealed mean value of NLR 2.3(±1.1) with a range of 0.6-4.0. Decreased total circulating eosinophil count (<40/cmm) was found in 6 (5.3%) cases. Thrombocytopenia was found in 31 (27.7%) cases, Elevated ESR was found in 53 (47.3%) cases; CRP value was increased in 47 (42.0%) cases. Increased serum ferritin was found in 29 (25.9%) cases. D-dimer was increased in 35 (31.3%) cases; Xray chest showed bilateral pneumonia in 26 (23.2%) cases. High resolution computed tomography (HRCT) of chest revealed ground glass opacities in 11(9.8%) cases. Conclusion: Multiple changes in laboratory findings were observed such as altered NLR, elevated acute phase reactants, increased seromarkers (S ferritin, D-dimers) and also opacities in chest imaging. Bang Med J Khulna 2020: 53 : 13-16